A revision of the Aphaenogaster phalangium complex (Hymenoptera: Formicidae: Myrmicinae) - Longino, John T.; Cover, Stefan (Zootaxa, 2004)
The Aphaenogaster phalangium complex is a lineage of rainforest ants endemic to Central America. The complex is revised and interpreted as two parapatric species, A. phalangium and A. araneoides, with extensive geographic variation. Character variation is discordant within species, but in some cases appears to vary in parallel between the two species, such that both species vary the same way in montane versus lowland sites. Aphaenogaster inermis Forel 1899, A. nitidiventris Forel 1912, and A. canalis Enzmann 1947 are synonymized under A. phalangium Emery 1890; and A. brevicollis Forel 1899 is synonymized under A. araneoides Emery 1890. The complex lacks winged queens and instead has ergatoid queens with enlarged postpetiole and gaster.